Metrological support of satellite-borne UV-spectrometry using a backscattering technique - Vashchenko, V.; Patlashenko, Zh.; Chernysh, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Methods and physicotechnical facilities for examination, calibration and metrological testing of the main power spectral characteristics (total spectral sensitivity, scattered stray radiation, dynamic range) of the vehicle-borne ozone UV spectrometers in the spectral range 250-350 nm are considered.